THE EFFECT OF DIALEARN (DIABETES E-LEARNING) ON THE LEVEL OF KNOWLEDGE ABOUT TYPE II DIABETES MELLITUS IN GODEAN YOGYAKARTA - Khirniq Qiqi Milataki; Ida Mardalena; Sapta Rahayu Noamperani; Rosa Delima Ekwantini (JTH: Journal of Technology and Health, 2026)
Diabetes mellitus (DM) is increasingly affecting adolescents due to unhealthy lifestyles, while their level of knowledge about DM remains low. This study aimed to determine the effect of DIALEARN (Diabetes E-Learning) on the level of knowledge about type 2 diabetes mellitus among tenth-grade students at SMK Negeri 2 Godean. This study employed a quasi-experimental design with a pretest-posttest control group design. The sampling technique used purposive sampling, involving 74 students divided into 37 students in the experimental group and 37 students in the control group. Data were analyzed using the Wilcoxon test and Mann–Whitney test. The results showed that before the intervention, most respondents had a low level of knowledge, and after the DIALEARN intervention, the majority improved to a moderate level, with some reaching a good level. The Mann–Whitney test showed a p-value of 0.020 (p < 0.05), indicating a significant effect of DIALEARN on the level of knowledge. In conclusion, DIALEARN (Diabetes E-Learning) has a significant effect on improving the level of knowledge about type 2 diabetes mellitus among tenth-grade students at SMK Negeri 2 Godean.